Prevalence of High Cadmium Levels in Major Metro Cities of India - Iyer, Sandhya; Sinkar, Prachi; Kallathiyan, Kallathikumar; Sengupta, Caesar (Asian Journal of Biological and Life Sciences, 2020)
Aim:High levels of cadmium in the human body may have severe adverse consequences affecting the pulmonary system and the kidney. The purpose of this report was to assess the frequency of high Cd levels in a population of Asian Indians in metro cities in India.Materials and Methods:Blood Cd levels from a total of 2,05,637 individuals were included. Technology of Inductively Coupled Plasma Mass Spectromtery was utilized for analysis.Results:Cd levels higher than 1.5 μg/L were found at a frequency of 1.9%. The frequency of high Cd levels was significantly different between males and females at p<0.0001. Of the top metro cities analysed in this study, the frequency of blood Cd levels above 1.5 μg/L was highest for Mumbai (9.5 %), Bangalore (7.5 %) and Hyderabad (4.4 %).Conclusion:Acknowledging the issue of toxicity and addressing the need for testing, monitoring will have to go a long way for charting management plans aligned with development goals.
Keywords: Blood Test; Cadmium; High levels; India; Mass Spectrometry